PENEGAKAN HUKUM PELAKU TINDAK PIDANA PENIPUAN ORDERAN FIKTIF OJEK ONLINE (ANALISIS PUTUSAN NOMOR 1507/PID.SUS/2018/PN.MDN DAN PUTUSAN NOMOR 143/PID.B/2018/PN.LMG) - Almas Shafira Mayzahira; Warasman Marbun; Mardani Mardani (Universitas Stikubank, 2023)
Crime is a social phenomenon that is the responsibility of the state and society because the more crimes that are committed, the greater the danger to the state and society. This study uses normative legal research methods which aim to analyze and evaluate court decisions related to law enforcement of perpetrators of fraudulent online motorcycle taxi ordering fraud. This method will involve literature study and document analysis, namely court decision number 1507/PID.SUS/2018/PN.MDN and decision number 143/PID.B/2018/PN.LMG which is related to the fraudulent case of fictitious online motorcycle taxi orders. The analysis was carried out using a statutory approach and legal theory related to criminal acts of fraud and related court decisions. The results of the analysis will be requested and presented in a narrative form that can provide a deeper understanding related to law enforcement against perpetrators of criminal acts of fraudulent online motorcycle taxi orders. Based on the author's analysis above of the two criminal court decisions in the field of Information and Electronic Transactions Law, it turns out that the authors found that it was very low and did not give a deterrent effect to perpetrators of the Electronic Information and Transactions Law and did not provide a sense of justice to victims. Keywords : Law enforcement, crime, fraud, fictitious order, online motorcycle taxi.